Turbidite paleoseismology in the Calabrian Arc Subduction Complex (Ionian Sea). (31st January 2013) - Polonia, A.; Panieri, G.; Gasperini, L.; Gasparotto, G.; Bellucci, L. G.; Torelli, L.
Abstract : [1] The Calabrian Arc subduction system is part of the Africa–Eurasia plate boundary, is one of the most seismically active regions in the Mediterranean Sea, and has been struck repeatedly by destructive historical earthquakes. In this study, we investigate the effects of historical earthquakes on abyssal marine sedimentation through the analysis of the turbidite record. We collected gravity cores in tectonically controlled basins where the eastern Mediterranean pelagic sequence is interbedded with resedimented units. Textural, micropaleontological, geochemical, and mineralogical signatures reveal three turbidite events in the last millennium. We dated the turbidite sequences from two different cores using different radiometric methods, whereas the average time interval between successive turbidite beds was estimated from pelagic sediment thickness and sedimentation rates; chronologies were refined through age modeling that provided age ranges (2 σ ) of each turbidite bed. The results suggest that turbidite emplacement was triggered by three historical earthquakes recorded in the area (i.e., the 1908, 1693, and 1169 events); their magnitude, epicentral location, and associated tsunamis support causative faults located in the Ionian Sea. The source for all the turbidites, as inferred from their mineralogy, is the metamorphic basement outcropping in southern Calabria and/or northeastern Sicily. Turbidite composition and cable breaks for the 1908 event have been used to infer likely traveling paths and seismogenic faults in the subduction system. Our findings suggest that Ionian Sea turbidites represent more than 80% of sedimentation and may be seabed archives of paleo‐earthquakes capable of reconstructing seismicity back in time, during several earthquake cycles. Key Points: We examine interplay between historical seismicity, mass failures and turbidites We reconstruct chronology of earthquake triggered turbidites in the Ionian Sea Turbidite composition has been used to reconstruct sediment source